Associated factors within the use of contraceptive methods in women of childbearing age between 15 to 49 years old according to a demographic survey in Peru - Vela-Ruiz, José M. (2022)
Background: Contraceptive methods are an important tool to achieve the desired family planning. Objective: To determine the factors associated within the use of contraceptive methods in women of childbearing age between 15 to 49 years old according to the ENDES 2018. Material and methods: Descriptive, observational, analytical and retrospective study. The sample, of the National Demographic Survey of Family Health (ENDES) 2018, to Peruvian women between 15 to 49 years old who responded to the contraceptive methods module was analyzed. Results: There is a higher prevalence of women using contraceptive methods in the urban area (PR = 1,046, CI: 1,037 - 1,054), according the marital status there is a high use in married women of contraceptive use (PR = 1,080 CI: 1,071 - 1,090), in the educational level it's obtained that women with higher education have a higher prevalence of contraceptive use (PR = 1,021, CI: 1,016 - 1,026) and, finally, that the age in the first sex relationship before 17 years has a higher prevalence (PR = 1,017 CI: 1,016 - 1,026). Conclusion: There is a positive association between living in an urban area, age of first sexual intercourse less than 17 years, being married and having high educational level in the use of contraceptive methods.